Detection of Hepatitis B Virus Pre-core Mutant by Allele Specific Polymerase Chain Reaction - Soewignjo Soemohardjo; Haris Widita; Zainul Muttaqin; Stephanus Gunawan; Mahendra Wijaya; Putu Aditya Wiguna; Shelly Olivia Rhamdiani (The Indonesian Society for Digestive Endoscopy, 2013)
Introduction: Mutation in pre-core region is characterized by negative HBeAg and positive anti-HBe despite active replications of the virus. The mutation has diagnostic and prognostic implications. Therefore, detectionof pre-core mutant is important. Standard diagnosis approach for detecting pre-core mutant is through DNA sequencing of hepatitis B virus (HBV) pre-core region. Unfortunately, DNA sequencing is not available in mostcenters. Hence, a simpler diagnostic approach is necessary.Method: An observational-analytic design study was performed. Detection of pre-core mutant was conducted in individuals with positive HBsAg and HBV DNA that had various patterns of HBeAg and anti HBe. HBsAg, HBeAg and anti-HBe was detected using immunochromatography technique. The HBV DNA was evaluated by using qualitative polymerase chain reaction (PCR) testing. PCR was done by three rounds of amplification with primers derived from wild type pre-core and mutant pre-core. Results: Of 25 sera with HBeAg negative, anti-HBe positive and HBV DNA positive, allele specific (AS) PCR pre-core mutant was detected in 20 (80%) sera. Two sera with HBeAg negative, anti HBe negative and HBV DNA positive were negative for pre-core mutant. Of 8 sera with HBeAg positive, anti HBe negative and HBV DNA positive, pre-core mutant was detected in 2 (25%) sera.Conclusion: Most of individuals with HBV DNA positive, HBeAg negative and anti-HBe positive have harbored pre-core mutant. The finding indicated that all patients with HBsAg positive, HBV DNA positive and HBeAg negative, but anti-HBe positive should be examined for the presence of pre-core mutant. Pre-core mutant is also found in HBeAg positive individual. Keywords: HBV, pre-core mutant, polymerase chain reaction